1995
DOI: 10.1183/09031936.95.08122185
|View full text |Cite
|
Sign up to set email alerts
|

Bronchogenic cyst presenting as mediastinal mass with pleural effusion

Abstract: Mediastinal bronchogenic cysts are usually identified on computed tomography (CT) as well-defined masses of variable density that may contain rim calcifications. Pleural effusion has never been described in association with these cysts.We report two cases of bronchogenic cysts with unusual presentation because of an association with a pleural effusion not explained by pulmonary infection. The patients were studied with CT scan (n=2) and magnetic resonance imaging (MRI) of the chest (n=1).In the first case, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…MATZINGER et al [21] reported a case of intrapulmonary bronchogenic cyst in a 16 year old girl presenting with pneumothorax. Other reported complications are pleural effusion [22,23], arrhythmias [24], stenosis of the pulmonary artery [25], unilateral ventilation-perfusion defect [26], pericardial and cardiac tamponade [27], carcinomatous [28] or sarcomatous transformation [29], and giant tension bronchogenic cyst [30]. Intrapulmonary bronchogenic cysts generally present as one of three different patterns on the chest radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…MATZINGER et al [21] reported a case of intrapulmonary bronchogenic cyst in a 16 year old girl presenting with pneumothorax. Other reported complications are pleural effusion [22,23], arrhythmias [24], stenosis of the pulmonary artery [25], unilateral ventilation-perfusion defect [26], pericardial and cardiac tamponade [27], carcinomatous [28] or sarcomatous transformation [29], and giant tension bronchogenic cyst [30]. Intrapulmonary bronchogenic cysts generally present as one of three different patterns on the chest radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…4 Bronchogenic cysts do not commonly cause pleural effusions. Three previous case reports describe pleural effusions associated with bronchogenic cysts in adult patients [5][6][7] but no cases were in children. In addition, the pleural effusion in these cases was clear fluid rather than hemorrhagic.…”
Section: Discussionmentioning
confidence: 97%
“…Percutaneous or transbronchial aspirations of the content of the cyst has also been used to treat bronchogenic cyst for high risk surgical patient [11]. "In all symptomatic patients, according to Mawatari et al the treatment should depend on the size and location of the cyst and their adherence to the surrounding structures" [12]. A small cyst, carinal in location and free from surrounding structures could be operated when diagnosed.…”
Section: Discussionmentioning
confidence: 99%